SELF-EVALUATION AND THE PERFORMANCE OF COMPETITIVE CREATIVE INDUSTRIES IN ERA 4.0 - Harini, Sri; Sudarijati, Sudarijati; Khanifah, Siti (Jurnal Aplikasi Manajemen, 2019)
Self-concept that describes employee behavior at work called self-evaluation can affect performance and competitive advantage. This study aims to analyze the influence of self-evaluation (self-esteem, self-efficacy, locus of control, and self-monitoring) of the performance's creative industry. The study used creative population industries. Sample researches were 40 persons as a manager or owner creative industry, proportional random sampling. The instrument test used validity and reliability test. Data were analyzed using multiple linear regressions were subsequently tested hypothesis by the F test and t-test. Based on multiple regressions analysis of the F test and t-test show that self-evaluation (self-esteem, self-efficacy, locus of control, and self-monitoring) simultaneously and partially have a positive and significant effect on performance of creative industry. No research was found on self-evaluation of the performance of creative industry entrepreneurs. Government policies in providing a sense of business security and training of creativity are urgently needed by creative industry players to face competition in imported products.